Anterograde Transport of Rab4-Associated Vesicles Regulates Synapse Organization in Drosophila. - Dey, S.; Banker, G.; Ray, K. (Cell reports, 2017)
Local endosomal recycling at synapses is essential to maintain neurotransmission. Rab4GTPase, found on sorting endosomes, is proposed to balance the flow of vesicles among endocytic, recycling, and degradative pathways in the presynaptic compartment. Here, we report that Rab4-associated vesicles move bidirectionally in Drosophila axons but with an anterograde bias, resulting in their moderate enrichment at the synaptic region of the larval ventral ganglion. Results from FK506 binding protein (FKBP) and FKBP-Rapamycin binding domain (FRB) conjugation assays in rat embryonic fibroblasts together with genetic analyses in Drosophila indicate that an association with Kinesin-2 (mediated by the tail domain of Kinesin-2?/KIF3A/KLP64D subunit) moves Rab4-associated vesicles toward the synapse. Reduction in the anterograde traffic of Rab4 causes an expansion of the volume of the synapse-bearing region in the ventral ganglion and increases the motility of Drosophila larvae. These results suggest that Rab4-dependent vesicular traffic toward the synapse plays a vital role in maintaining synaptic balance in this neuronal network.